Hak Cipta atas Karya di Internet: Pengaturan dan Upaya Perlindungannya - Budi Agus Riswandi (Fakultas Hukum Universitas Islam Indonesia, 2007)
The born of digital image creation in the Internet stipulates legal impacts. One of the impacts is copy rights law. The copy rights law should be able to respond the digital image phenomena in the internet. The Indonesian Copy rights law is regulated on the Act No. 19 /2002. In fact, this Act has regulated digital creations in the internet. This indicates that the Act provides protection to the creations. Is it true ?